Bioactivity-guided isolation of antimicrobial metabolite from Xylaria sp. (May 2020) - Rakshith, Devaraju; Gurudatt, Doddahosuru Mahadevappa; Yashavantha Rao, H.C.; Chandra Mohana, N.; Nuthan, B.R.; Ramesha, K.P.; Satish, Sreedharamurthy
Graphical abstract: Highlights: Bioactivity guided fractionation using bioautography and chromatography. Antimicrobial activity against panel of both human and phytopathogens was observed. The bioactive moiety was identified as xylobovide-9-methyl ester by spectroscopy. The present study facilitates strain prioritization by bioautography approach. Abstract: Symbiotic plant-microbe metabolic interactions not only have beneficial effects on plants but also contribute to rich, unmatched and complex chemical biodiversity with biological potential. Systematic delineated bioprospecting of fungal diversity associated with Ficus pumila Linn (Moraceae) for antimicrobial metabolite revealed Xylaria sp. FPL-25(M). The present study describes bioactivity guided fractionation prioritized for antimicrobial potential. Thus, chemical investigation of culture broth of Xylaria sp. FPL-25(M) by bioactivity guided fractionation with spectroscopic techniques revealed bioactive metabolite xylobovide-9-methyl ester. The xylobovide-9-methyl ester exhibited broad-spectrum antimicrobial activity. However, Gram-positive bacteria and fungi were more susceptible than Gram-negative bacteria. The present study results represent bioassay-based screening strategy which facilitates rapid, efficient and reliable approach for endophytic strain prioritization for novel bioactive molecules.